INVESTIGATION OF THE LUBRICITY OF DIESEL FUEL AND AVIATION FUEL ON A HIGH-PRESSURE FUEL PUMP (ADVANCES IN MECHANICAL ENGINEERING AND TRANSPORT, 2021)
This paper presents comparative experimental study’s results of diesel fuel and aviation fuel effect on operational properties of a high-pressure fuel pump of a common rail injection system. The two identical fuel injection systems mounted on a test bed of the fuel injection pumps were prepared for the experimental durability tests. The lubricity properties of diesel fuel and aviation fuel (Jet-A1) were studied using the High-Frequency Reciprocating Rig (HFRR) method. The values of wear scar diameter (WSD) obtained with Jet-A1 fuels were compared to the respective values measured with the reference diesel fuel. The microscopic photographs of the wear scar diameters obtained on above mentioned fuels are presented in the paper. The test results showed that long-term (about 300 hours) using aviation fuels produced a negative effect on the durability of the high-pressure fuel pump. Due to the wear of plunger-barrel units the decrease in the fuel delivery rate occurred of about 6.7 % operating with aviation fuel. The average friction coefficients of Jet-A1 fuels were higher than that of the normal diesel fuel.Keywords: diesel fuel, aviation Jet-A1 fuel, lubricity, plunger-barrel units, wear scar diameter.